Accelerator for reaction of high-silicon aluminosilicates with water
By using specific chemicals as accelerators, the reaction performance of high-silicon silicates and water is improved, and the problems of ordinary Portland cement substitution and high CO2 emissions are solved, providing safer and more environmentally friendly building materials adhesives .
Patent Information
- Application Number
- CN202380034817.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-30
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to effectively replace ordinary Portland cement as a binder for building materials, especially under the premise of reducing high CO2 emissions and avoiding the use of strong alkaline chemicals, the activator of high silicon aluminosilicate is poor. .
Alkanoamines, sugars, sugar acids, carboxylic acids and their salts, amino acids and their salts, sulfamic acids, glyoxaldehyde, acetylacetone, catechol, nitris(methylphosphonic acid) or mineral salts are used As a promoter for the reaction of high-silicon aluminosilicates with water, the chemicals are used to improve their strength and rheology in building materials.
The performance of the high aluminosilicate and water mixture in terms of compressive strength, rheology and water demand is significantly improved, and the fluidity attenuation is reduced, providing a safer and more environmentally friendly alternative binder solution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to an accelerator for the reaction of high-silica aluminosilicates with water, a binder comprising high-silica aluminosilicates and the accelerator, and the use of the binder in building materials. Background of the Invention
[0002] Cementitious building materials, especially concrete or mortar, rely on cementitious materials as binders. Cementitious binders are usually mineral hydraulic binders, the most abundant of which is cement, especially ordinary Portland cement (OPC). However, the use of cement, especially ordinary Portland cement, has a high environmental footprint. One major reason is the high CO2 emissions associated with the manufacture of cement. Therefore, many efforts have been made to at least partially replace cement as a binder for building materials.
[0003] One possibility is to use materials with cementitious properties, so-called supplementary cementitious materials (SCMs). Supplementary cementitious materials can be hydraulic, pozzolanic and / or latently hydraulic. Supplementary cementitious materials known for many years include limestone, steelmaking slag, calcined clay, natural pozzolans such as volcanic ash, silica fume or fly ash.
[0004] It is well known in the art that supplementary cementitious materials can be activated to function as hydraulic binders.
[0005] For example, WO 2020 / 025504 (St. Gobain) discloses binders based on clay minerals and teaches that flocculants, especially polycationic polymers, can improve the cohesion of such clay-based binders.
[0006] WO 2019 / 110134 (Ecocem) discloses slag-based binders with an activator for the slag / water reaction selected from alkali metal carbonates, mineral waste, silica fume, rice husk ash and / or phosphoric acid. Soluble chlorides, fluorides and / or sulfates are mentioned as suitable co-activators. Chelating agents selected from phosphonates, phosphates, carboxylates and amines are also disclosed.
[0007] One class of supplementary cementitious materials are the aluminosilicates and, for example, the high aluminosilicates.
[0008] It is well known in the art that aluminosilicates can be activated and reacted with water to form so-called geopolymers, for example by overalkaline components such as alkali metal silicates, alkali metal hydroxides or lime (see WO 2010 / 079414 (S. Alter)).
[0009] There remains a need for alternative accelerators for auxiliary cementitious materials, especially for high aluminosilicates, to enable such high aluminosilicates to be used in hydraulic compositions. Generally, strongly alkaline chemicals and / or accelerators that result in high dust emissions during handling should be avoided. Summary of the invention
[0010] An object of the present invention is to provide an accelerator for the reaction of high-silicon-aluminosilicate with water. Specifically, the accelerator should have high activation potential, good usability, low basicity and safe operation.
[0011] Another object of the present invention is to provide a high aluminosilicate based binder which can be used to replace OPC based binders.
[0012] Another object of the present invention is to provide building materials, especially concrete and mortar compositions, based on high-silicon-aluminosilicate-based binders.
[0013] It has surprisingly been found that chemicals selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids and their salts, amino acids and their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof are suitable accelerators for the reaction of high-silica aluminosilicates with water.
[0014] Therefore, the present invention relates to the use of an accelerator for the reaction of a high-silica-aluminosilicate with water, wherein the accelerator is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids and their salts, amino acids and their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0015] It has been found that the accelerators according to the invention lead to an increase in the strength, in particular the compressive strength, of a mixture comprising a high aluminosilicate, water and accelerator after a given point in time (as measured in accordance with EN 12190) compared to the strength, in particular the compressive strength, of a mixture of a high aluminosilicate and water in the same proportions but without the addition of accelerator and measured after the same time. The time is always measured from the moment of addition of water to the high aluminosilicate.
[0016] It has further been found that the accelerator of the present invention has a positive effect on the rheological properties of a mixture of high aluminosilicate and water. Positive effect herein means that the viscosity of a mixture comprising high aluminosilicate, water and accelerator is lower than the viscosity of a mixture of high aluminosilicate and water in the same proportion but without the addition of accelerator.
[0017] It has further been found that the accelerator of the present invention has a positive effect on the water demand of a mixture of a high aluminosilicate and water. Positive effect herein means that after mixing a mixture comprising a high aluminosilicate, water and an accelerator, the water demand to reach a given consistency is lower than the water demand to reach the same consistency of a mixture of a high aluminosilicate and water in the same proportions but without the addition of an accelerator.
[0018] It is further found that the accelerator of the present invention can have a positive effect on the decay of fluidity over time after wet mixing. The positive effect herein means that the fluidity loss of the mixture containing high aluminosilicate, water and accelerator is lower than the fluidity loss of the mixture of high aluminosilicate and water in the same proportion but without the addition of accelerator.
[0019] Further aspects of the invention are the subject matter of the independent claims. Preferred embodiments of the invention are the subject matter of the dependent claims. DETAILED DESCRIPTION
[0020] In a first aspect, the present invention relates to the use of an accelerator for the reaction of a high-silica-alumina silicate with water, wherein the accelerator is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids and their salts, amino acids and their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0021] The high aluminosilicate in the present invention is a material with pozzolanic properties and / or latent hydraulic properties having aluminosilicate as a component, characterized by a high content of silicon dioxide (SiO2) in its chemical composition. The chemical composition of the high aluminosilicate can be determined by XRF as described in EN 196-2:2013. The high aluminosilicate of the present invention may contain other oxides besides SiO2 and Al2O3. Other oxides may be, for example, boron oxide, calcium oxide, titanium oxide, iron oxide, zinc oxide. The term "oxide" generally also includes respective hydroxides and / or mixed oxides / hydroxides.
[0022] The high content of SiO2 is expressed in wt% relative to the total dry weight of the high aluminosilicate. Thus, the high aluminosilicate of the present invention is characterized in that the content of SiO2 is not less than 40 wt%, preferably not less than 50 wt%, relative to the total dry weight of the corresponding high aluminosilicate, and is determined by XRF as described in EN 196-2:2013.
[0023] The high aluminosilicate of the present invention is characterized by a chemical composition in which the weight ratio of SiO2 to Al2O3 is 50:50-100:0, preferably 65:35-95:5. The preferred high aluminosilicate of the present invention has a weight ratio of (SiO2+Al2O3) to CaO of 75:25-100:0, preferably 83:17-100:0, more preferably 90:10-99:1, while the weight ratio of SiO2 to Al2O3 is 50:50-100:0, preferably 65:35-95:5.
[0024] Suitable high-silicon aluminosilicates in the present invention are selected from glassy pumice, glassy volcanic ash, zeolitic tuff, diatomaceous earth, fly ash, silica fume, kiln dust, microsilica, pyrolytic silica, precipitated silica, burning oil shale, combustion residues of organic matter and mixtures thereof. Fly ash is especially fly ash of Class F according to Standard ASTM C618.
[0025] In this context, the high-silicon-aluminosilicate is not a steelmaking slag, in particular not ground granulated blast furnace slag (GGBS) or basic oxygen furnace slag (BOS), and is not a Class C fly ash according to standard ASTM C618. In addition, in this context, the high-silicon-aluminosilicate is not a clay mineral or calcined clay.
[0026] The particle size of high-silicon-aluminosilicates can be analyzed by sieve analysis, for example, as described in standard ASTM C 136 / C136M. This method separates fine particles from coarser particles by passing the material through a number of sieves of different mesh sizes. The material to be analyzed is vibrated through a series of sequentially decreasing sieves, using a single horizontal, vertical or rotational motion or a combination thereof. As a result, the percentage of particles retained on a sieve of a given size is given.
[0027] Another measure of the fineness of the high aluminosilicate is the Blaine surface area. The Blaine surface area can be determined according to NF EN 196-6. According to a preferred embodiment, the Blaine surface area of the high aluminosilicate is 1000-8000 cm 2 / g, preferably 2000-6000cm 2 / g, more preferably 3000-5000cm 2 / g. This is because the accelerator will promote the reaction of the high aluminosilicate with water to the extent that a coarser SCM can also be used. Coarser SCM can have the advantages of better availability and lower cost compared to fine SCM. However, a high aluminosilicate with a higher specific surface area can also be used.
[0028] The present invention relates to the application of accelerators in the reaction of high silicoaluminosilicate with water. When high silicoaluminosilicate reacts with water, hydration reaction occurs to form different mineral phases. Thus, water and SCM are consumed, hardened and strength is generated. Therefore, a suitable method for measuring the reaction of high silicoaluminosilicate with water is to measure strength, especially compressive strength. The higher the compressive strength, the higher the reaction process, i.e., more mineral phases are formed. Therefore, the promotion of the reaction of high silicoaluminosilicate with water can be determined by comparing the strength, especially compressive strength, of different mixtures after a given reaction time, for example, after 2 days, after 7 days and / or after 28 days. The accelerator for the reaction of high silicoaluminosilicate with water causes the strength, especially compressive strength, of a mixture comprising high silicoaluminosilicate, water and accelerator after a given time point, which is compared to the strength, especially compressive strength of a mixture of high silicoaluminosilicate and water in the same proportion but without the addition of accelerator and measured after the same time. This time is always measured from the moment when water is added to high silicoaluminosilicate. A suitable procedure for measuring compressive strength is described in EN 12190.
[0029] The accelerator for the reaction of high aluminosilicate with water is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids and their salts, amino acids and their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0030] One class of suitable accelerators is alkanolamines. The alkanolamines are preferably selected from monoethanolamine, diethanolamine, triethanolamine (TEA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA), isopropanolamine, diisopropanolamine, triisopropanolamine (TIPA), N-methyldiisopropanolamine (MDIPA), N-methyldiethanolamine (MDEA), tetrahydroxyethylethylenediamine (THEED) and tetrahydroxyisopropylethylenediamine (THIPD), and mixtures of two or more of these alkanolamines.
[0031] Preferred alkanolamines are triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA) and ethanoldiisopropanolamine (EDIPA). Particularly preferred alkanolamines are diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and triisopropanolamine (TIPA).
[0032] Another suitable promoter is sugar. "Sugar" in the sense of the present invention is a carbohydrate with an aldehyde group. In a particularly preferred embodiment, sugar belongs to monosaccharides or disaccharides. Examples of sugars include, but are not limited to, glyceraldehyde, threose, erythrose, xylose, lyxose, ribose, arabinose, allose, altrose, glucose, mannose, gulose, idose, galactose, tallow sugar, fructose, sorbose, lactose, maltose, sucrose, lactulose, trehalose, cellobiose, chitobiose, isomaltose, palatinose, mannobiose, raffinose and xylobiose. Sugar can also be used in the form of dextrin, vinasse or molasses. D, L-type and both forms of sugar are also preferred. Particularly preferred sugars are fructose, mannose, maltose, glucose, galactose, dextrin, vinasse and molasses.
[0033] Another suitable promoter is sugar acid or its salt. In the context of the present invention, "sugar acid" is a monosaccharide with a carboxyl group. It can belong to any category of aldonic acid, ursonic acid, uronic acid or aldaric acid. Preferably, it is aldonic acid. Examples of useful sugar acids related to the present invention include, but are not limited to, gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucolic acid and saccharic acid. Sugar acid can be in the form of free acid or salt. According to an embodiment, sugar acid salts can be salts formed with metals of Groups Ia, IIa, Ib, IIb, IVb, VIIIb of the Periodic Table of Elements. Preferred sugar acid salts are salts formed with alkali metals, alkaline earth metals, iron, cobalt, copper or zinc. Especially preferred are salts formed with sodium, potassium and calcium. Sugar acids of D-, L-type and both forms are also preferred. Especially preferred sugar acids are gluconic acid and its salts, especially sodium gluconate.
[0034] Another suitable accelerator is an amino acid or a salt thereof. The amino acid is preferably selected from glycine, lysine, glutamate, glutamic acid, aspartic acid, polyaspartic acid, methionine, nitrilotriacetic acid (NTA), iminodisuccinic acid, methylglycine-N,N-diacetic acid and N,N-bis(carboxymethyl)glutamic acid, ethylenediaminedisuccinic acid (EDDS), ethylenediaminetetraacetic acid (EDTA), hexamethylenediaminetetraacetic acid (HEDTA), diethylenetriaminepentaacetic acid (DTPA) or a salt thereof. Alkali metal salts or alkaline earth metal salts are particularly preferred. In particular, the salt is selected from tetrasodium N,N-bis(carboxymethyl)glutamate, trisodium methylglycine-N,N-diacetic acid, tetrasodium iminodisuccinate (IDS), trisodium ethylenediaminedisuccinate, tetrasodium ethylenediaminetetraacetic acid and tetrasodium hexamethylenediaminetetraacetic acid.
[0035] Another suitable promoter is a carboxylic acid or a salt thereof. The term "carboxylic acid" refers to any organic molecule with a carboxylic acid or carboxylate group except a sugar acid as described above or an amino acid as described above. Particularly preferred carboxylic acids are formic acid, glycolic acid, citric acid, lactic acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid and salicylic acid. The carboxylic acid can be in the form of a free acid or a salt. According to an embodiment, a carboxylate can be a salt formed with a metal of Group Ia, IIa, Ib, IIb, IVb, VIIIb of the Periodic Table of Elements. Preferred sugar acid salts are salts formed with alkali metals, alkaline earth metals, iron, cobalt, copper or zinc. Particularly preferred are salts formed with sodium, potassium and calcium. Preferred carboxylates are calcium malonate, calcium succinate, calcium lactate, potassium citrate and sodium citrate.
[0036] Another class of suitable promoters is reducing agents. In this context, reducing agents are materials with a reduction potential below 0.77 V measured under standard conditions relative to a standard reference hydrogen half-cell. That is, suitable reducing agents have a reduction potential below Fe 3+ / Fe 2+ The half-cell potential of the reductant is preferably selected from thiosulfates, thiocyanates and sulfides, preferably selected from sodium thiocyanate, sodium thiosulfate or potassium sulfide. In this context, the reductant does not belong to any of the above-mentioned groups of alkanolamines, sugars, sugar acids, carboxylic acids and their salts or amino acids and their salts.
[0037] Other suitable accelerators are aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid) and etidronic acid.
[0038] Another suitable accelerator is a mineral salt. In this context, a mineral salt is a salt selected from alkali metal or alkaline earth metal nitrates, alkali metal or alkaline earth metal nitrites, alkali metal or alkaline earth metal chlorides, aluminum sulfate, aluminum chloride, sodium sulfate and calcium sulfate. Particularly preferred mineral salts are sodium chloride, calcium nitrite, calcium nitrate, calcium chloride, magnesium chloride, aluminum sulfate, aluminum chloride, sodium sulfate and calcium sulfate.
[0039] According to an embodiment, the accelerator is selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA), fructose, mannose, maltose, glucose, galactose, dextrin, lees, molasses, gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucic acid, saccharic acid and its sodium, potassium or calcium salt, formic acid, glycolic acid, citric acid, lactic acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, salicylic acid. Acids and their sodium, potassium or calcium salts, glycine, glutamic acid, aspartic acid, polyaspartic acid, tetrasodium iminodisuccinate (IDS), diethylenetriaminepentaacetic acid (DTMA), nitrilotriacetic acid (NTA), aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, sodium thiocyanate, sodium chloride, calcium nitrite, calcium nitrate, calcium chloride, magnesium chloride, calcium sulfate, aluminum sulfate, aluminum chloride, sodium sulfate, thiosulfates (especially sodium thiosulfate), thiocyanates and sulfides (especially potassium sulfide).
[0040] According to a particularly preferred embodiment, the accelerator is selected from diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA), lactic acid, calcium lactate, oxalic acid, malonic acid, succinic acid, adipic acid, malic acid, tartaric acid, citric acid, sodium citrate, potassium citrate, gluconic acid, sodium gluconate, glycine, aminosulfonic acid, glyoxal, acetylacetone, catechol, tetrasodium iminodisuccinate (IDS), nitrilotriacetic acid (NTA) and calcium sulfate.
[0041] According to a further preferred embodiment, the accelerator is a mixture of two alkanolamines or a mixture of an alkanolamine and at least one further accelerator which is different from an alkanolamine.
[0042] According to a particularly preferred embodiment, the accelerator is a mixture of diethanolisopropanolamine (DEIPA) and triisopropanolamine (TIPA).
[0043] According to a further embodiment, the accelerator is a mixture of an alkanolamine selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and / or methyldiethanolamine (MDEA), in particular TIPA and / or DEIPA, and an additional accelerator selected from fructose, mannose, maltose, glucose, galactose, dextrin, vinasse, molasses, gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucic acid, saccharic acid and its sodium, potassium or calcium salts, formic acid, glycolic acid, citric acid, Citric acid, lactic acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, salicylic acid and its sodium, potassium or calcium salts, glycine, glutamic acid, aspartic acid, polyaspartic acid, tetrasodium iminodisuccinate (IDS), diethylenetriaminepentaacetic acid (DTMA), nitrilotriacetic acid (NTA), aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, sodium thiocyanate, sodium chloride, calcium nitrite, calcium nitrate, calcium chloride, magnesium chloride, calcium sulfate, aluminum sulfate, aluminum chloride, sodium sulfate, thiosulfates (especially sodium thiosulfate), thiocyanates and sulfides (especially potassium sulfide).
[0044] A preferred embodiment of the accelerator of the present invention is a mixture of TIPA and / or DEIPA with at least one of lactic acid, malic acid, tartaric acid, citric acid, sodium citrate, potassium citrate, malonic acid, succinic acid, adipic acid, glycine, aminosulfonic acid or its salt, catechol, sugar (especially fructose), tetrasodium iminodisuccinate (IDS), calcium chloride and calcium sulfate.
[0045] An especially preferred embodiment of the accelerator of the present invention is a mixture of TIPA and / or DEIPA with a sugar, preferably fructose.
[0046] A further particularly preferred embodiment of the accelerator according to the invention is a mixture of TIPA and / or DEIPA with citric acid or its salts, in particular with citric acid, sodium citrate, potassium citrate or calcium citrate.
[0047] According to a further embodiment, the accelerator is a mixture of an alkanolamine selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and / or methyldiethanolamine (MDEA), in particular TIPA and / or DEIPA, and two further accelerators, the first of which is selected from sugars, in particular fructose, mannose, maltose, glucose or galactose, and the second of which is selected from mineral salts and reducing agents, preferably selected from sodium thiocyanate, sodium chloride, calcium chloride, magnesium chloride, calcium nitrite, calcium nitrate, aluminum sulfate, aluminum chloride, sodium sulfate, calcium sulfate, sodium thiosulfate and potassium sulfide.
[0048] A further particularly preferred embodiment of the accelerator according to the invention is a mixture of TIPA and / or DEIPA with a sugar, preferably fructose, and with a carboxylic acid or a salt thereof, preferably citric acid, sodium citrate, potassium citrate or calcium citrate.
[0049] A further particularly preferred embodiment of the accelerator of the invention is a mixture of TIPA and / or DEIPA with sugar, preferably fructose, and with at least one of sodium thiocyanate, sodium chloride, aluminum sulfate or calcium nitrite.
[0050] A further particularly preferred embodiment of the accelerator according to the invention is a mixture of TIPA and / or DEIPA with calcium sulfate or calcium nitrate.
[0051] According to a further embodiment, the accelerator is a mixture of an alkanolamine selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and / or methyldiethanolamine (MDEA), in particular TIPA and / or DEIPA, and two further accelerators, the first of which is selected from sugars, in particular fructose, mannose, maltose, glucose or galactose, and the second of which is selected from sugar acids, carboxylic acids and aminosulfonic acids, in particular gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucic acid, saccharic acid, salicylic acid and its sodium, potassium or calcium salts, formic acid, glycolic acid, citric acid, lactic acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid and its sodium, potassium or calcium salts.
[0052] According to a further embodiment, the accelerator is a mixture of an alkanolamine selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and / or methyldiethanolamine (MDEA), in particular TIPA and / or DEIPA, and three additional accelerators, the first of which is selected from sugars, preferably fructose, mannose, maltose, glucose or galactose, and the second additional accelerator is selected from sugar acids, carboxylic acids, and aminosulfonic acid, preferably gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucic acid, saccharic acid and their sodium, potassium or calcium salts, formic acid, glycolic acid, citric acid, lactic acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, salicylic acid and their sodium, potassium or calcium salts, and the third additional accelerator is selected from mineral salts and reducing agents, preferably selected from sodium thiocyanate, sodium chloride, calcium chloride, magnesium chloride, calcium nitrite, calcium nitrate, aluminum sulfate, aluminum chloride, sodium sulfate, calcium sulfate, sodium thiosulfate and potassium sulfide.
[0053] According to an embodiment, the accelerator of the present invention is used in neat, undiluted form.
[0054] According to different embodiments, the accelerator of the present invention is used as an admixture or as a part of an admixture. The admixture comprises or consists of the accelerator or a mixture of accelerators and optional other ingredients. These other ingredients can be, for example, solvents, especially water, biocides or pigments. Therefore, the accelerator of the present invention can also be used in a dispersed or dissolved state, especially dispersed or dissolved in water.
[0055] When the accelerator of the present invention is a mixture of two or more of the above-mentioned accelerators or an admixture is used, the accelerator or admixture can be present as a single component, a two-component or a multi-component composition. This means that the individual components forming the accelerator or admixture of the present invention can be present in a container in an already mixed state to form a single component composition. The accelerator can also be present in two or more spatially separated containers to form a two-component or multi-component composition. This may be beneficial to the shelf life of the accelerator mixture. This may also promote the mixing of accelerators with variable ratios of high silicoaluminosilicate and water. When the accelerator of the present invention is present in a two-component or multi-component composition, they can be pre-mixed or added separately at the same time point or added separately at different time points.
[0056] According to an embodiment, the accelerators of the present invention are added in a total amount of 0.005-25% by weight relative to the total dry weight of the high aluminosilicate. The total amount refers to the sum of the weight % of all accelerators present.
[0057] According to a preferred embodiment, the alkanolamine is added in a total amount of 0.005-5 wt%, preferably 0.01-3 wt%, relative to the total dry weight of the high aluminosilicate.
[0058] According to a preferred embodiment, sugar is added in a total amount of 0.005-5 wt%, preferably 0.01-3 wt%, relative to the total dry weight of the high aluminosilicate.
[0059] According to a preferred embodiment, the carboxylic acid is added in a total amount of 0.005-5 wt%, preferably 0.01-3 wt%, relative to the total dry weight of the high aluminosilicate.
[0060] According to a preferred embodiment, the amino acid is added in a total amount of 0.005-5 wt%, preferably 0.01-3 wt%, relative to the total dry weight of the high aluminosilicate.
[0061] According to a preferred embodiment, the reducing agent, especially sodium thiocyanate, is added in a total amount of 0.05-10 wt %, preferably 0.1-6 wt %, relative to the total dry weight of the high silicoaluminosilicate.
[0062] According to a preferred embodiment, the total amount of mineral salt added is 0.005-25% by weight, preferably 0.1-10% by weight or 2-25% by weight, more preferably 0.1-6% by weight or 10-25% by weight, relative to the total dry weight of the high-silicon-aluminosilicate. The range of 2-25% by weight, preferably 10-25% by weight, especially refers to the use of sodium chloride, aluminum sulfate or calcium sulfate as mineral salt.
[0063] According to an embodiment, any one of sulfamic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid) and etidronic acid is added in an amount of 0.05-10 wt %, preferably 0.1-6 wt %, relative to the total dry weight of the high aluminosilicate.
[0064] It has been found that too high a dosage of accelerator reduces the accelerating effect relative to high aluminosilicates.
[0065] In case a mixture of two or more accelerators as described above is used, it is preferred that the weight ratio of any one selected from the following (if present): - alkanolamine to sugar, - alkanolamine to carboxylic acid, - alkanolamine to amino acid, - sugar to amino acid, - carboxylic acid to amino acid, or - alkanolamine, sugar, carboxylic acid and amino acid to any one selected from aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid) and etidronic acid is in the range of 1:50 to 50:1, preferably 1:20 to 20:1.
[0066] Where a mixture of two or more accelerators as described above is used, it is preferred that the weight ratio of any selection or combination of alkanolamines, sugars, carboxylic acids, amino acids, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid) and etidronic acid (if present) to any selection or combination of mineral salts and reducing agents is in the range of 1:5000 to 1:1000, preferably 1:2500 to 1:1000.
[0067] The reaction of high-silicon-aluminosilicate with water in the presence of a co-binder can be promoted. In particular, the reaction of high-silicon-aluminosilicate with water in the presence of Portland cement, limestone, gypsum or a mixture thereof can be promoted. Therefore, according to an embodiment, the use as described above is characterized in that the reaction of high-silicon-aluminosilicate with water is promoted in the presence of Portland cement and optionally limestone and / or gypsum.
[0068] The present invention also relates to a method for promoting the reaction of high aluminosilicate with water, the method comprising the step of mixing at least one high aluminosilicate with water and an accelerator, wherein the accelerator is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids and their salts, amino acids and their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0069] All features and embodiments described above also apply in this case.
[0070] On the other hand, the present invention also relates to a binder based on high-silicon-aluminosilicate, which is preferably used as a binder in concrete or mortar, the binder comprising or consisting of: a) at least one high-silicon-aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolitic tuff or a mixture thereof, b) at least one accelerator for the reaction of the high-silicon-aluminosilicate with water, the accelerator being selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or their salts, amino acids or their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof, c) optionally at least one auxiliary binder, d) optionally, other additives different from b).
[0071] It should be understood that any embodiment, especially the embodiment involving the above-mentioned preferred high aluminosilicate and at least one accelerator, also applies to the binder based on high aluminosilicate of the present invention. In particular, preferably, the high aluminosilicate has a SiO2 content of not less than 40% by weight, preferably not less than 50% by weight, relative to the total dry weight of the corresponding high aluminosilicate and determined by XRF as described in EN 196-2:2013.
[0072] According to some embodiments, the high aluminosilicate-based binder of the present invention comprises an accelerator selected from the group consisting of diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA), lactic acid, calcium lactate, oxalic acid, malonic acid, succinic acid, adipic acid, malic acid, tartaric acid, citric acid, gluconic acid, sodium gluconate, glycine, aminosulfonic acid, glyoxal, acetylacetone, catechol, tetrasodium iminodisuccinate (IDS), nitrilotriacetic acid (NTA) and calcium sulfate.
[0073] According to a further embodiment, the high aluminosilicate based binder of the present invention comprises an accelerator which is a mixture of diethanolisopropanolamine (DEIPA) and triisopropanolamine (TIPA).
[0074] According to a further embodiment, the high aluminosilicate based binder of the present invention comprises an accelerator which is a mixture of an alkanolamine selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and / or methyldiethanolamine (MDEA), especially TIPA and / or DEIPA, and an additional accelerator selected from lactic acid, malic acid, tartaric acid, citric acid, malonic acid, succinic acid, adipic acid, glycine, aminosulfonic acid or its salts, catechol, sugar, especially fructose, tetrasodium iminodisuccinate (IDS), calcium chloride and calcium sulfate.
[0075] According to a further embodiment, the high aluminosilicate based binder of the present invention comprises an accelerator which is a mixture of an alkanolamine selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and / or methyldiethanolamine (MDEA), in particular TIPA and / or DEIPA, and two further accelerators, the first of which is selected from sugars, in particular fructose, mannose, maltose, glucose or galactose, and the second of which is selected from mineral salts, preferably sodium chloride, calcium chloride, calcium nitrite, calcium nitrate, aluminum sulfate, aluminum chloride, sodium sulfate and calcium sulfate.
[0076] The auxiliary binder herein is an inorganic binder selected from cement, gypsum, lime, calcined magnesia, caustic magnesia, alumina, latent hydraulic binder, limestone and / or pozzolan. The latent hydraulic binder and / or pozzolan used as auxiliary binder is chemically different from the high-silicon-aluminum silicate as defined above. In particular, slags such as ground granular blast furnace slag and basic oxygen slag, clay minerals, especially calcined clay, and / or Class C fly ash are latent hydraulic binders and / or pozzolans, which are chemically different from the high-silicon-aluminum silicate of the present invention and can be used as auxiliary binders. Cement can especially be CEM I, CEM II and CEM IV type Portland cements as described in standard EN 197-1 except CEM II / AS and CEM II / BS, calcium aluminate cements as described in standard EN 14647, and / or calcium sulphoaluminate cements. The term "gypsum" is intended to include various forms of CaSO4, in particular anhydrite CaSO4, alpha- and beta-hemihydrated CaSO4 and dihydrated CaSO4. The term "lime" is meant to include natural hydraulic lime, formulated lime, hydraulic lime and air lime as described in standard EN 459-1:2015. The term "alumina" represents aluminum oxides, aluminum hydroxides and / or aluminum hydroxyhydroxides such as gibbsite and boehmite, calcined or flash-calcined aluminum oxides, aluminum oxides obtained by the Bayer process, hydratable aluminum oxides such as amorphous mesophase aluminum oxides and rho-phase aluminum oxides. The limestone is preferably according to standard EN 197-1:2011. Preferably, the auxiliary binder is selected from Portland cement, calcium aluminate cement, calcium sulfoaluminate cement, gypsum, hydraulic lime, gas-hardening lime, calcined magnesia, caustic magnesia, calcined alumina, hydratable alumina, aluminum hydroxide, slags such as ground granulated blast furnace slag and basic oxygen slag, limestone, clay minerals, especially calcined clay and / or Class C fly ash. Particularly preferably, the auxiliary binder is selected from Portland cement, limestone and / or gypsum.
[0077] According to an embodiment in which a co-binder is present, in the binder based on high aluminosilicate, the weight ratio of high aluminosilicate (especially glassy pumice, glassy volcanic ash, zeolite tuff, burned oil shale) to co-binder is 1:19-19:1, preferably 1:9-15:1, more preferably 1:6-12:1, still more preferably 1:5-9:1, highly preferably 1:3-6:1, especially 1:1-5:1.
[0078] Optionally, the slag-based binder of the present invention additionally comprises other additives other than accelerators for the reaction of high-silicon aluminosilicate with water. According to an embodiment, such other additives are selected from plasticizers, superplasticizers, shrinkage reducers, air entrainers, degassing agents, stabilizers, viscosity regulators, thickeners, water reducers, retarders, waterproofing agents, fibers, foaming agents, defoamers, redispersible polymer powders, dust removers, chromate reducing agents, pigments, biocides, corrosion inhibitors and steel passivators.
[0079] According to some embodiments, the binder based on high aluminosilicates of the present invention comprises or consists of (in each case relative to the total dry weight of the binder): a) 75-99.995% by weight, preferably 95-99.99% by weight, of at least one high aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolite tuff, burned oil shale, b) 0.005-25% by weight, preferably 0.01-5% by weight, of at least one accelerator for the reaction of the at least one high aluminosilicate with water, wherein the accelerator is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or salts thereof, amino acids or salts thereof, sulfamic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0080] According to a further embodiment, the binder based on high aluminosilicates according to the invention comprises or consists of (in each case relative to the total dry weight of the binder): a) 74.9-99.895% by weight, preferably 74.99-99.89% by weight, of at least one high aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolitic tuff, burned oil shale, b) 0.005-25% by weight, preferably 0.01-5% by weight, of at least one accelerator for the reaction of the at least one high aluminosilicate with water, c) 0.1-25% by weight of a co-binder selected from cement or lime, wherein the accelerator is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or salts thereof, amino acids or salts thereof, sulfamic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0081] According to a further embodiment, the binder based on high aluminosilicates according to the invention comprises or consists of (in each case relative to the total dry weight of the binder): a) 74.9-99.895% by weight, preferably 74.99-99.89% by weight, of at least one high aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolitic tuff, burned oil shale, b) 0.005-25% by weight, preferably 0.01-5% by weight, of at least one accelerator for the reaction of the at least one high aluminosilicate with water, c) 0.1-25% by weight of a co-binder selected from calcium sulfoaluminate cement, wherein the accelerator is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or salts thereof, amino acids or salts thereof, sulfamic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0082] According to a further embodiment, the binder based on high-silicon-aluminosilicates according to the invention comprises or consists of (in each case relative to the total dry weight of the binder): a) 49.995-99.895% by weight, preferably 49.99-99.89% by weight, of at least one high-silicon-aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolitic tuff, burned oil shale, b) 0.005-25% by weight, preferably 0.01-5% by weight, of at least one accelerator for the reaction of the at least one high-silicon-aluminosilicate with water, c) 0.1-50% by weight of a co-binder selected from the group consisting of a combination of calcium aluminate cement and calcium sulfate or a combination of calcium sulfoaluminate cement and calcium sulfate, wherein the accelerator is selected from the group consisting of alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or salts thereof, amino acids or salts thereof, sulfamic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
[0083] In any of these embodiments, preferred promoters are the same as described above.
[0084] In yet another aspect, the present invention also relates to a building material, especially mortar or concrete, comprising the high-silicon-aluminosilicate-based binder as described above.
[0085] The present invention therefore also relates in particular to a building material, preferably a concrete or mortar composition, which comprises or consists of (in each case relative to the total dry weight of the building material): a) 5 to 95% by weight, preferably 5 to 60% by weight, of a binder based on a high-silicon-aluminosilicate, the binder comprising or consisting of: a1) at least one high-silicon-aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolitic tuff, burned oil shale, a2) at least one accelerator for the reaction of the at least one high-silicon-aluminosilicate with water, the accelerator being selected from the group consisting of alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or salts thereof, amino acids or salts thereof, sulfamic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof, preferably selected from the accelerators as preferably described above, b) 5 to 95% by weight, preferably 30 to 90% by weight, of at least one aggregate, c) 0-90% by weight, preferably 5-30% by weight, of at least one auxiliary binder which is different from the binder based on high aluminosilicate a) and which is selected from cement, gypsum, lime, calcined magnesia, caustic magnesia, alumina, limestone, clay minerals, calcined clay, slag, class C fly ash, d) 0-10% by weight of other additives, and e) optionally water in an amount to achieve a water:dry components mass ratio of 0.1-0.6, preferably 0.2-0.5, in particular 0.2-0.35.
[0086] The binders, co-binders and other additives based on high aluminosilicates are preferably as described above. In particular, it is preferred that the high aluminosilicates have a SiO content of not less than 40% by weight, preferably not less than 50% by weight, relative to the total dry weight of the corresponding high aluminosilicates and measured by XRF as described in EN 196-2:20 13.
[0087] It may be preferred to combine two or more additional additives in the building material of the invention. Thus, the building material of the invention comprises at least one high-silica aluminosilicate as described above and an accelerator as described above, the accelerator being selected from the group consisting of alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or salts thereof, amino acids or salts thereof, aminosulfonic acid, glyoxal, acetylacetone, catechol, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotris(methylphosphonic acid) and etidronic acid, alkali or alkaline earth metal nitrates or nitrites or chlorides, aluminum sulfate, aluminum chloride, sodium sulfate, calcium sulfate, or mixtures thereof.
[0088] According to a preferred embodiment, the building material comprises 5-90 wt. %, preferably 5-30 wt. %, of at least one auxiliary binder selected from the group consisting of Portland cement, calcium aluminate cement, calcium sulfoaluminate cement, gypsum, calcium sulfate, lime, ground calcium carbonate, pozzolans, caustic magnesium oxide and latent hydraulic binders, wherein the pozzolans and latent hydraulic binders do not contain high-silica aluminosilicates.
[0089] Aggregate can be any material that does not react in the hydration reaction of the binder. Aggregate can be any aggregate commonly used in building materials. Typical aggregates are, for example, rock, crushed stone, gravel, sand. Aggregate can also be fine aggregate or filler. Aggregates that can be used in the present invention can have any shape and size that such aggregates are commonly encountered. Particularly preferred aggregate is sand. Sand is a naturally occurring granular material that is composed of finely divided rock or mineral particles. It has various forms and sizes. Examples of suitable sand are quartz sand, river sand or crushed aggregate. Suitable sand is, for example, described in standard ASTM C778 or EN196-1.
[0090] According to the embodiment, the aggregate may also be one or more of the following (i)-(iv):
[0091] (i) Biogenic material, preferably of plant origin, more preferably of plant origin consisting essentially of cellulose and / or lignin, in particular of hemp, flax, cereal straw, oats, rice, rape, corn, sorghum, flax, miscanthus, rice husks, sugar cane, sunflower, kenaf, coconut, olive pits, bamboo, wood or mixtures thereof. According to an embodiment, the biogenic material of plant origin has a defined form, which is preferably selected from fibers, fibrils, dust, meal, powder, shavings, pith, in particular pith of sunflower, corn, rapeseed, and mixtures thereof.
[0092] (ii) Synthetic non-mineral materials, preferably selected from the group consisting of thermoplastics, thermosetting plastics or resins, elastomers, rubbers, textile fibers, plastic materials reinforced with glass or carbon fibers. Synthetic non-mineral materials may be filled or unfilled.
[0093] (iii) Aggregates of inorganic nature coming from the deconstruction of civil engineering or building structures, preferably selected from the group comprising or consisting of: waste concrete, mortar, bricks, natural stone, asphalt, tiles, tiles, aerated concrete, clinker, waste metal.
[0094] (iv) Aggregates of organic nature from industrial product recycling, in particular difficult to recycle composite materials, especially recycled insulation materials. Particularly preferred examples are polystyrene, polyurethane, epoxy resins, phenolic resins, wood insulation materials and mixtures thereof.
[0095] Most preferably, the aggregate is in particulate form.
[0096] Throughout the present invention, when calculating the mass ratio of water: dry ingredients, the total dry weight of the high aluminosilicate-based binder and the optional co-binder should be taken into account. No correction should be made to compensate for any degree of hydraulic hardness. The term dry ingredients herein relates to all powdered components of the composition, especially the high aluminosilicate-based binder, aggregates and co-binders.
[0097] The weight ratio of water to binder can be adjusted to control the rheology and / or strength of the wet building material. Higher amounts of water will result in a more fluid wet composition, while lower amounts of water will result in a pasty wet composition. The rheology can be adjusted by the amount of water to produce a wet composition with a rheology ranging from self-leveling to very thick. Generally, lower amounts of water will also result in increased strength.
[0098] According to an embodiment, in the presence of a co-binder, the weight ratio of the high silicoaluminosilicate-based binder to the co-binder in the building material as described above is 1:19-19:1, preferably 1:9-15:1, more preferably 1:6-12:1, still more preferably 1:5-9:1, highly preferably 1:3-6:1, especially 1:1-5:1.
[0099] According to an embodiment, the hydraulic composition according to the invention comprises 15 to 85% by weight, preferably 35 to 80% by weight and in particular 50 to 75% by weight of sand, each based on the total dry weight of the composition.
[0100] The further additives may be any additive commonly used in the mortar and concrete industry. In particular, the further additives may be selected from plasticizers, superplasticizers, shrinkage reducers, air entraining agents, deaerators, stabilizers, viscosity modifiers, thickeners, water reducers, retarders, waterproofing agents, fibers, foaming agents, defoamers, redispersible polymer powders, dust removers, chromate reducing agents, pigments, biocides, corrosion inhibitors and steel passivators.
[0101] According to an embodiment, the building material of the invention, in particular concrete or mortar, comprises at least one superplasticizer selected from lignin sulfonates, sulfonated vinyl copolymers, polynaphthalene sulfonates, sulfonated melamine formaldehyde condensates, polyethylene oxide phosphonates, polycarboxylate ethers (PCE) or mixtures thereof. Preferably, the building material of the invention, in particular concrete or mortar, comprises PCE. Such PCE is particularly suitable for allowing good processability of hydraulic compositions even at low water contents.
[0102] According to an embodiment, the building material (especially concrete or mortar) of the present invention comprises at least one thickener selected from the group consisting of starch, pectin, pullulan, modified starch, cellulose, modified cellulose (such as carboxymethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, methylhydroxyethylcellulose), casein, xanthan gum, diutan gum, welan gum, galactomannans (such as guar gum, tara gum, fenugreek gum, locust bean gum or cassia gum), alginates, tragacanth gum, dextran, polydextrose, layered silicates (such as sepiolite, bentonite or vermiculite) and mixtures thereof.
[0103] According to an embodiment, the building material of the present invention, especially concrete or mortar comprises at least one redispersible polymer powder. The term redispersible polymer powder refers to a powder containing a polymer and forming a stable dispersion after being introduced into water. Redispersible polymer powders include not only polymers, but also generally include mixtures thereof with, for example, protective colloids, emulsifiers and carrier materials. Redispersible polymer powders can be manufactured, for example, by spray drying of polymer dispersions as described in patent application EP1042391. Suitable redispersible powders are purchased from Wacker Chemie AG, for example, under the trade name Vinnapas. The use of redispersible powders of synthetic organic polymers is preferred for the context of the present invention. Synthetic organic polymers in the context of the present invention can be prepared by free radical polymerization of monomers selected from ethylene, propylene, butylene, isoprene, butadiene, styrene, acrylonitrile, acrylic acid, methacrylic acid, acrylates, esters of methacrylic acid, vinyl esters, and vinyl chloride. Preferred synthetic polymers are copolymers synthesized by two or more, preferably two different monomers. The sequence of the copolymer can be alternating, block or random. Preferred synthetic organic polymers are copolymers of vinyl acetate and ethylene, vinyl acetate and ethylene and methyl methacrylate, vinyl acetate and ethylene and vinyl esters, vinyl acetate and ethylene and acrylates, vinyl chloride and ethylene and vinyl laurate, vinyl acetate and vinyl versatate, acrylates and styrene, acrylates and styrene and butadiene, acrylates and acrylonitrile, styrene and butadiene, acrylic acid and styrene, methacrylic acid and styrene, styrene and acrylates, styrene and methacrylates. The glass transition temperature (Tg) of the synthetic organic polymer may vary within a wide range, and the Tg of suitable synthetic organic polymers may be, for example, from -50°C to +60°C, preferably from -45°C to +35°C, more preferably from -25°C to +15°C.
[0104] The building materials of the present invention, especially concrete or mortar, may also contain liquid additives. Such liquid additives may be mixed with the dry ingredients of the building materials and cause the building materials to have a powdery or pasty consistency. The liquid additive may be, for example, an aqueous solution or dispersion of a plasticizer or superplasticizer. When water or an aqueous additive is added to the building materials to be dry mixed, the amount of water should be limited to no more than 0.5% by weight relative to the total dry weight of the building materials.
[0105] According to a preferred embodiment, the building material, in particular the concrete or mortar preparation, comprises (in each case relative to the total dry weight of the building material):
[0106] 5-95 wt. %, preferably 5-60 wt. % of a binder based on a high aluminosilicate, the binder comprising: a1) at least one high aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolitic tuff, burned oil shale, a2) at least one accelerator for the reaction of the at least one high aluminosilicate with water, the accelerator being selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or salts thereof, amino acids or salts thereof, sulfamic acid, glyoxal, acetylacetone, catechol, sulfamic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid) and etidronic acid, mineral salts or mixtures thereof,
[0107] 5 to 95% by weight, preferably 30 to 90% by weight, of at least one aggregate,
[0108] 0-90 wt. %, preferably 5-30 wt. %, of at least one auxiliary binder selected from the group consisting of Portland cement, calcium aluminate cement, calcium sulphoaluminate cement, gypsum, hydraulic lime, gas-hardening lime, calcined magnesia, caustic magnesia, ground granulated blast furnace slag, basic oxygen slag, limestone, clay minerals, in particular calcined clay, Class C fly ash,
[0109] 0-10 wt% of other additives, and
[0110] Optionally water, in an amount to achieve a water:dry ingredients mass ratio of 0.1-0.6, preferably 0.2-0.5, in particular 0.2-0.35.
[0111] All preferred features described above also apply in this case.
[0112] According to a further embodiment, the present invention also relates to a building material, preferably a concrete or mortar composition, which comprises or consists of (in each case relative to the total dry weight of the building material): a) 5-95% by weight, preferably 5-60% by weight, of a binder based on a high-silicon-aluminosilicate, the binder comprising or consisting of: a1) at least one high-silicon-aluminosilicate, preferably glassy pumice, glassy pozzolana, zeolitized tuff, burned oil shale, a2) at least one accelerator for the reaction of the at least one high-silicon-aluminosilicate with water as described above, b) 5-95% by weight, preferably 30-90% by weight of at least one aggregate, c) optionally 20-80% by weight, preferably 40-80% by weight of at least one auxiliary binder selected from Portland cement, calcium aluminate cement, calcium sulphoaluminate cement, gypsum or mixtures thereof, d) 0-10% by weight of other additives, and e) Optionally water, in an amount to achieve a water:dry ingredients mass ratio of 0.1-0.6, preferably 0.2-0.5, in particular 0.2-0.35.
[0113] The building material of the present invention can be prepared by mixing the components, in particular the binder based on high-silicon-aluminosilicate, aggregate and optionally the co-binder, other additives and water by conventional methods. Suitable mixers are, for example, horizontal single-shaft mixers, twin-shaft paddle mixers, vertical shaft mixers, ribbon kneaders, orbital mixers, can-changing mixers, tumbling containers, vertical stirring chambers or air-stirring operations. Mixing can be continuous or batchwise.
[0114] According to a preferred embodiment, the building material of the invention is a one-component mixture. This means that all the individual components are mixed with one another. One-component compositions are particularly easy to handle and exclude the risk of the user mixing or incorrectly metering the individual components.
[0115] However, it is in principle possible to provide the building material according to the invention as a two-component or even multi-component composition. A two-component or multi-component composition allows, for example, the building material to be adjusted to the specific application.
[0116] Typically, the dry building material according to the invention is mixed with water only shortly before its application. This is because the building material according to the invention will begin to harden when it comes into contact with water. It is therefore particularly preferred to first prepare the dry building material, in particular the dry mortar or dry concrete as described above, and then mix the dry building material with water at or near the application site.
[0117] The method and apparatus for mixing dry building materials with water are not particularly limited and are known to those skilled in the art. Mixing can be continuous, semi-continuous or batchwise. Continuous mixing offers the advantage of high material throughput.
[0118] Therefore, the building material of the present invention, especially concrete or mortar, may be a dry building material or a wet building material.
[0119] According to an embodiment, the dry building material is in particular a dry mortar, a premixed mortar or a dry concrete. According to a further embodiment, the dry composition as described above is prepared at the job site, for example by mixing at least one component with other components of the dry composition and / or by mixing two or more components of a multi-component material.
[0120] The building material of the present invention can be a cementitious tile adhesive, a grouting material, a self-leveling pad, a self-leveling covering layer, a plaster, a repair mortar, a thin joint mortar or concrete for brickwork, a leveling layer, a wall leveler for internal or external use, a non-shrinking grouting, a thin joint mortar, a waterproof mortar, or an anchoring mortar. The cementitious tile adhesive is especially in accordance with the EN12004-1 standard. The grouting material is especially in accordance with the standard EN13888. The self-leveling pad or self-leveling covering layer is especially in accordance with the standard EN 13813. The plaster is especially in accordance with the standard EN 998-1. The repair mortar is especially in accordance with the standard EN1504-3. The thin joint mortar or concrete for brickwork is especially in accordance with the standards EN 998-2 and EN 206-1. The leveling layer is especially in accordance with the standard EN 13813. The non-shrinking grouting is especially in accordance with the standard EN 1504-6. The thin-joint mortar is in particular in accordance with standard EN 998-2. The waterproofing mortar is in particular in accordance with standard EN 1504-2. The anchoring mortar is in particular in accordance with standard EN 1504-6.
[0121] When mixed with water, the building material of the present invention, especially concrete or mortar, will begin to set and harden. The setting and hardening of the building material proceeds over time, thereby developing physical properties, such as compressive strength.
[0122] In a final aspect, the invention relates to a hardened body obtained by curing a concrete or mortar composition as described above, and in which a binder based on a high-silicon-aluminosilicate or building material has been mixed with water in such an amount that the mass ratio of water: dry ingredients is 0.1-0.6, preferably 0.2-0.5, in particular 0.2-0.35.
[0123] It will be understood that any of the embodiments, in particular those relating to the preferred high aluminosilicate and at least one accelerator described above, also apply in this regard. In particular, preferably, the high aluminosilicate has a SiO2 content of not less than 40 wt.-%, preferably not less than 50 wt.-%, relative to the total dry weight of the corresponding high aluminosilicate and determined by XRF as described in EN 196-2:2013.
[0124] The curing conditions are not particularly limited and are known to those skilled in the art. In particular, curing can be carried out at a temperature of 5° C. to 200° C. and a pressure of 1 atm to 12 atm. Curing can be carried out at normal pressure, or in a water-saturated atmosphere or in any other atmosphere. Preferably, curing is carried out at a pressure of 1 atm and 5° C. to 35° C. Example The following raw materials were used in the examples:
[0125] Triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA), NaCl, dextrin (from potato starch), sucrose and sodium gluconate (Na-gluconate) were purchased from Sigma Aldrich and used as received. Portland clinker, limestone and gypsum were ground to about 3500 cm-1 according to standard EN 197-1:2011, where the Portland clinker was ground to about 3500 cm-1 without any additions. 2 / g of Blaine surface area. Glassy pozzolans are used as high aluminosilicates. The high aluminosilicates used (aluminosilicates 1-3) have a SiO2 content of 45-57% by weight, an Al2O3 content of 16-21% by weight, a CaO content of 6-16% by weight, and a Fe2O3 content of 4-9% by weight (determined by XRF as described in EN 196-2:2013).
[0126] To prepare the following examples, 450 g of each mixture of Portland clinker, limestone, pozzolan, and gypsum (as indicated in the table below) were mixed with 225 g of mixing water to give a water / binder ratio of 0.5. The various admixtures indicated in the table below were added together with the mixing water (ppm relative to the total dry weight of the binder). Mixing was carried out on a mortar mixer according to standard EN 196. After 28 days of curing, tests for determining the compressive strength were carried out according to EN 196-1:2016 and EN 12190:1998 using prisms (40×40×160 mm). The first 24 hours of curing were carried out at 20°C and at least 95% rh. The rest of the curing was carried out at 20°C and in water saturated with Ca(OH)2.
[0127] Table 2: Examples 1-3, 5, 7, 9, 11 (comparative), Examples 4, 6, 8, 10, 12 (inventive)
[0128] Table 2 continued
[0129] From the results in Table 2 above, it can be seen that the mixtures of TEA / TIPA, TIPA / DEIPA / NaCl / dextrin, TEA / TIPA / NaCl / dextrin and TEA / TIPA / NaCl / dextrin / sucrose resulted in a higher rate of increase in compressive strength when used with cement containing high aluminosilicates compared to cement containing the same amount of limestone.
[0130] Table 3: Examples 13-15, 17, 19, 21, 23 (comparative), Examples 16, 18, 20, 22, 24 (inventive)
[0131] Table 3: continued
[0132] From the results in Table 3 above, it can be seen that the mixtures of TEA / TIPA, TEA / TIPA / sodium gluconate, TIPA / DEIPA and TEA / TIPA / dextrin and TIPA / dextrin result in a higher rate of increase in compressive strength when used with cement containing high aluminosilicates compared to cement containing the same amount of limestone.
[0133] Table 4: Examples 25-27, 29, 31, 33, 35, 37, 39, 41 (comparative), Examples 28, 30, 32, 34, 36, 38, 40, 42 (of the present invention)
[0134] Table 4 continued
[0135] Table 4 continued
[0136] Table 4 continued
[0137] From the results in Table 4 above, it can be seen that TEA, TIPA, DEIPA and EDIPA, and mixtures of any of these with dextrin, result in a higher increase in compressive strength when used with cements in which some of the cement is replaced with high aluminosilicates, compared to cements that do not contain high aluminosilicates.
[0138] The above examples show that the reaction of high aluminosilicate with water can be promoted by using alkanolamines, sugars, sugar acids, mineral salts or mixtures thereof.
Claims
1. A promoter for the reaction of a high-silicon-aluminosilicate with water, wherein the promoter is selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids and their salts, amino acids and their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof.
2. The use according to claim 1, It is characterized in that The high aluminosilicate has not less than 40 wt. %, preferably not less than 50 wt. %, of SiO, relative to the total dry weight of the corresponding high aluminosilicate and determined by XRF as described in EN 196-2:2013. 2 content.
3. The use according to at least one of the preceding claims, It is characterized in that The promoter is selected from the group consisting of triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA), fructose, mannose, maltose, glucose, galactose, dextrin, lees, molasses, gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucic acid, saccharic acid and its sodium, potassium or calcium salt, formic acid, glycolic acid, citric acid, lactic acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, Salicylic acid and its sodium, potassium or calcium salts, glycine, glutamic acid, aspartic acid, polyaspartic acid, tetrasodium iminodisuccinate (IDS), diethylenetriaminepentaacetic acid (DTMA), nitrilotriacetic acid (NTA), aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, sodium thiocyanate, sodium chloride, calcium nitrite, calcium nitrate, calcium chloride, magnesium chloride, calcium sulfate, aluminum sulfate, aluminum chloride, sodium sulfate, thiosulfates (especially sodium thiosulfate), thiocyanates and sulfides (especially potassium sulfide).
4. The use according to at least one of claims 1 to 2, It is characterized in that The accelerator is a mixture of two alkanolamines or a mixture of an alkanolamine and at least one additional accelerator different from an alkanolamine.
5. The use according to claim 4, It is characterized in that The alkanolamine is selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and methyldiethanolamine (MDEA), especially TIPA and / or DEIPA, and the at least one additional accelerator is selected from fructose, mannose, maltose, glucose, galactose, dextrin, vinasse, molasses, gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucic acid, saccharic acid and its sodium, potassium or calcium salts, formic acid, glycolic acid, citric acid, lactic acid, malic acid, tartaric acid, Oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, salicylic acid and its sodium, potassium or calcium salts, glycine, glutamic acid, aspartic acid, polyaspartic acid, tetrasodium iminodisuccinate (IDS), diethylenetriaminepentaacetic acid (DTMA), nitrilotriacetic acid (NTA), aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, sodium thiocyanate, sodium chloride, calcium nitrite, calcium nitrate, calcium chloride, magnesium chloride, calcium sulfate, aluminum sulfate, sodium sulfate, aluminum chloride, thiosulfates (especially sodium thiosulfate), thiocyanates and sulfides (especially potassium sulfide).
6. The use according to claim 4, It is characterized in that The alkanolamine is selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and methyldiethanolamine (MDEA), especially TIPA and / or DEIPA, and two further accelerators are present, the first further accelerator being selected from sugars, especially fructose, mannose, maltose, glucose or galactose, and the second further accelerator being selected from mineral salts and reducing agents, preferably selected from sodium thiocyanate, sodium chloride, calcium chloride, magnesium chloride, calcium nitrite, calcium nitrate, aluminum sulfate, aluminum chloride, sodium sulfate, calcium sulfate, sodium thiosulfate and potassium sulfide.
7. The use according to claim 4, It is characterized in that The alkanolamine is selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and methyldiethanolamine (MDEA), especially TIPA and / or DEIPA, and two further accelerators are present, the first further accelerator being selected from sugars, especially fructose, mannose, maltose, glucose or galactose, and the second further accelerator being selected from sugar acids, carboxylic acids and aminosulfonic acids, especially gluconic acid, ascorbic acid, neuraminic acid, glucuronic acid, galacturonic acid, iduronic acid, mucic acid, saccharic acid, salicylic acid and its sodium, potassium or calcium salts, formic acid, glycolic acid, citric acid, lactic acid, malic acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid and its sodium, potassium or calcium salts.
8. The use according to claim 4, It is characterized in that The alkanolamine is selected from triethanolamine (TEA), triisopropanolamine (TIPA), diethanolisopropanolamine (DEIPA), ethanoldiisopropanolamine (EDIPA) and methyldiethanolamine (MDEA), especially TIPA and / or DEIPA, and there are three additional accelerators, the first additional accelerator is selected from sugars, preferably fructose, mannose, maltose, glucose or galactose, and the second additional accelerator is selected from sugar acids, carboxylic acids and aminosulfonic acids, preferably gluconic acid, ascorbic acid, The third additional accelerator is selected from mineral salts and reducing agents, preferably selected from sodium thiocyanate, sodium chloride, calcium chloride, magnesium chloride, calcium nitrite, calcium nitrate, aluminum sulfate, aluminum chloride, sodium sulfate, calcium sulfate, sodium thiosulfate and potassium sulfide.
9. The use according to at least one of the preceding claims, It is characterized in that The accelerator is added in a total amount between 0.005-25 wt % relative to the total dry weight of the high aluminosilicate.
10. The use according to at least one of the preceding claims, It is characterized in that The reaction of high aluminosilicates with water is promoted in the presence of Portland cement and optionally limestone and / or gypsum.
11. A high-silicon-aluminosilicate based binder preferably used as a binder in concrete or mortar, the binder comprising or consisting of composition: a) at least one high-silica-aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolite tuff, burned oil shale, b) at least one accelerator for the reaction of the at least one high-silica-aluminosilicate with water, the accelerator being selected from the group consisting of alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or their salts, amino acids or their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof, c) optionally at least one co-binder, d) optionally, other additives different from those in b).
12. A binder based on high aluminosilicate according to claim 11, Features The accelerator is selected from the accelerators of claim 3, or the accelerator is a mixture as defined in any one of claims 4-8.
13. A building material, preferably a concrete or mortar composition, comprising or consisting of (in each case relative to the total dry weight of the building material): a) 5 to 95% by weight, preferably 5 to 60% by weight, of a binder based on a high-silicon-aluminosilicate, the binder comprising or consisting of composition: a1) at least one high-aluminosilicate, preferably glassy pumice, glassy volcanic ash, zeolitic tuff, burned oil shale, a2) at least one accelerator for the reaction of the at least one high-aluminosilicate with water, the accelerator being selected from alkanolamines, reducing agents, sugars, sugar acids, carboxylic acids or their salts, amino acids or their salts, aminosulfonic acid, glyoxal, acetylacetone, catechol, nitrilotri(methylphosphonic acid), etidronic acid, mineral salts or mixtures thereof, preferably selected from the accelerators or mixtures of accelerators as defined in any one of claims 4 to 9, b) 5 to 95% by weight, preferably 30 to 90% by weight, of at least one aggregate, c) 0 to 90% by weight, preferably 5 to 30% by weight, of at least one auxiliary binder, the auxiliary binder being different from the binder based on the high-aluminosilicate a), and the auxiliary binder being selected from cement, gypsum, lime, calcined magnesia, caustic magnesia, alumina, limestone, clay minerals, calcined clay, slag, class C fly ash, d) 0-10% by weight of other additives, and e) optionally water in an amount such that a mass ratio of water:dry ingredients is 0.1-0.6, preferably 0.2-0.5, in particular 0.2-0.
35.
14. The building material according to claim 13, It is characterized in that The building material comprises 5-90% by weight, preferably 5-30% by weight, of at least one auxiliary binder selected from the group consisting of Portland cement, calcium aluminate cement, calcium sulfoaluminate cement, gypsum, hydraulic lime, gas-hardening lime, calcined magnesia, caustic magnesia, ground granulated blast furnace slag, basic oxygen slag, limestone, clay minerals, in particular calcined clay, Class C fly ash.
15. A binder based on high-silicon-aluminosilicate according to claim 11 or a building material according to any one of claims 13 to 14, Features A co-binder is present, and the weight ratio of high-silica aluminosilicate, especially glassy pumice, glassy volcanic ash, zeolite tuff, burnt oil shale, to the co-binder is 1:19-19:1, preferably 1:9-15:1, more preferably 1:6-12:1, still more preferably 1:5-9:1, highly preferably 1:3-6:1, especially 1:1-5:
1.
16. A hardened body obtained by curing a high-silicon-aluminosilicate-based binder as claimed in claims 11 to 12 or 15 or a building material as claimed in at least one of claims 13 to 14, wherein the binder or building material has been mixed with water in an amount such that the mass ratio of water: dry powder is 0.1 to 0.6, preferably 0.2 to 0.5, in particular 0.2 to 0.35.
